Perjanjian Baku Pembiayaan Murabahah Perbankan Syariah Indonesia - Hamidah, Siti; Sukarmi; Yuliati; Suwardiyati, Rumi (Faculty of Law, Universitas Brawijaya, 2022)
Buying and selling products with murabahah contracts are ranked first in financing practices in Indonesian sharia banks but receive particular attention regarding conformity with sharia principles and the position of consumers from a consumer protection perspective. In the framework of realizing